Multifocal repetitive TMS for motor and mood symptoms of Parkinson disease: A randomized trial. (1st November 2016) - Brys, Miroslaw; Fox, Michael D.; Agarwal, Shashank; Biagioni, Milton; Dacpano, Geraldine; Kumar, Pawan; Pirraglia, Elizabeth; Chen, Robert; Wu, Allan; Fernandez, Hubert; Shukla, Aparna Wagle; Lou, Jau-Shin; et al.
Abstract : Objective: To assess whether multifocal, high-frequency repetitive transcranial magnetic stimulation (rTMS) of motor and prefrontal cortex benefits motor and mood symptoms in patients with Parkinson disease (PD). Methods: Patients with PD and depression were enrolled in this multicenter, double-blind, sham-controlled, parallel-group study of real or realistic (electric) sham rTMS. Patients were randomized to 1 of 4 groups: bilateral M1 ( + sham dorsolateral prefrontal cortex [DLPFC]), DLPFC ( + sham M1), M1 + DLPFC, or double sham. The TMS course consisted of 10 daily sessions of 2, 000 stimuli for the left DLPFC and 1, 000 stimuli for each M1 (50 × 4-second trains of 40 stimuli at 10 Hz). Patients were evaluated at baseline, at 1 week, and at 1, 3, and 6 months after treatment. Primary endpoints were changes in motor function assessed with the Unified Parkinson's Disease Rating Scale-III and in mood with the Hamilton Depression Rating Scale at 1 month. Results: Of the 160 patients planned for recruitment, 85 were screened, 61 were randomized, and 50 completed all study visits. Real M1 rTMS resulted in greater improvement in motor function than sham at the primary endpoint ( p < 0.05). There was no improvement in mood in the DLPFC group compared to the double-sham group, as well as no benefit to combining M1 and DLPFC stimulation for either motor or mood symptoms. Conclusions: In patients with PD with depression, M1 rTMS is an effective treatment of motor symptoms, while mood benefit after 2 weeks of DLPFC rTMS is not better than sham. Targeting both M1 and DLPFC in each rTMS session showed no evidence of synergistic effects. ClinicalTrials.gov identifier: NCT01080794. Classification of evidence: This study provides Class I evidence that in patients with PD with depression, M1 rTMS leads to improvement in motor function while DLPFC rTMS does not lead to improvement in depression compared to sham rTMS.